Mechanism of Post-hypertonic Lysis of Isolated Rat Hepatocytes During Rehydration - Kuleshova, L. G. (Problems of Cryobiology and Cryomedicine, 2006)
The kinetics of cell volume control in the isolated rat hepatocytes when varying an extracellular medium tonicity, simulating the processes of dehydration and rehydration of cells under the conditions of growth and melting of extracellular ice crystals was studied with light microscopy. Post-hypertonic lysis of rat hepatocytes was shown to be realised by either discrete release of a part of endocellular content, or its continuous outflow to extracellular environment. Cell osmotic activity under following cyclic osmotic loadings testified to a preservation of membrane semi-permeable properties and â€œhealingâ€ of the membrane pore.